(untitled) (Annals of Medical Research, 2024)
Aim: To evaluate Pan-immune inflammation value (PIV), Systemic inflammatory response index (SIRI) and Systemic immune inflammation index (SII) for the comparison of twin pregnancies with singleton pregnancies. Materials and Methods: The cohort study was conducted retrospectively in the Ankara Etlik City Hospital Obstetrics and Perinatology Clinics between October 2022 and August 2024. Women with singleton pregnancies whose follow-up and delivery took place in the same tertiary center were included in the control group (Group I). Women with twin pregnancies who were followed up and delivered at the same tertiary center were included in the case group (Group II). The inflammation-based indices (PIV, SIRI and SII) of the two groups were compared with each other. Results: 221 twin pregnancies were identified after screening according to the inclusion/exclusion criteria, the remaining 138 pregnancies were sorted chronologically by date of birth. The first 115 twin pregnancies in the ranking list that were eligible for the study according to the power analysis were included in group II. For each twin pregnancy that was eligible for Group II, the first singleton pregnancy in the rank order of files that met the inclusion criteria was selected for Group I as the control group. The groups differed significantly in hemoglobin and PIV values (p=0.045 vs. 0.007). There were no significant differences in demographic and inflammatory indices in mono- and di-chorionic pregnancies. Conclusion: Low PLT and high LYM in twins lead to a statistically significant decrease in PIV, even if this is not statistically significant. We can say that this reflects the physiological inflammatory/immune response of pregnancy. However, our findings need to be supported by multicenter and prospective randomized controlled trials.